DAMPAK PSIKOLOGI TERHADAP ANAK AKIBAT PERNIKAHAN SIRRI DI DESA MANCON KECAMATAN WILANGAN KABUPATEN NGANJUK - Ahmad Mubbin; Dwi Ari Kurniawati; Humaidi Kaha (Jurnal Hikmatina, 2022)
Marriage is a matter that has wide implications in the legal relationship between husband and wife. With the marriage, a bond that contains rights and obligations arises. This paper chooses the type of qualitative research, the method used by the author is to see directly the phenomena in the field, summarize the data obtained, and arrange them according to research needs. Focus on objects with clear indicators and variables. Researchers use primary data that is generated directly from the field, observations and interviews with informants while normative library data or written rules are used as secondary data. Findings Their psychological impact on limiting their association with the people around them and their parents during a serial marriage was tested. When at school there is a report card taking, the mother must have taken it because the father does not have guardianship rights for the child. Some children also take social deviant actions such as taking part in illegal motorcycle races just for fun and an outlet because at home, their parents lack love. So they do things that are fun for themselves, don't see what they do as positive or negative.